Epistimologi Pendidikan Seks dalam al-Quran - Hamka Hasan (ILMU USHULUDDIN, 2019)
The characteristics of sex education in the Qur’an are preventive, universal, realistic-accurate. Preventive because the Qur’an has warned from the beginning to avoid negative sex so as not to fall into the humiliation as it has befalling the past. Universal because the Qur’an explains thoroughly all the problems about sex from before someone was born until he died. Realistic because the Qur’an recognizes that sex cannot be separated from human problems. The method of writing this paper is the Mawḍū’ī Interpretation (thematic) by identifying the verses of the Qur’an related to the theme. The purpose of writing this paper is to explain to the reader the concept of the Qur’an about sex education. To realize this goal, this paper outlines the meaning, purpose, object, phase, benefits of sex education in the Qur’an. The steps of the research are: identifying sexual problems that exist in society, then linking with the values contained in the Qur’an.